Port, maritime and hinterland development in Southeast Asia - Muhammad Subhan; Sabariah Yaakub; Ahmad Bashawir Abdul Ghani (Penerbit Universiti Utara Malaysia, 2014)
This book addresses myriad of issues and challenges in the field of port, maritime and hinterland development in Southeast Asia from multidisciplinary perspectives. Instead of focusing on only certain aspects of the maritime discipline, the book presents a range of different viewpoint from business and management, historical development, geography, law, and others. Although the book is made in the form of an edited book, readers will benefit and gain knowledge on many important issues in the field of port, maritime and hinterland development in Southeast Asia.